The impact of select factors on the price of gold in Malaysia / Jehan Nabila Azizan and Khadijah Mahsan - Azizan, Jehan Nabila; Mahsan, Khadijah (Faculty of Business and Management, 2014)
This paper analysed the impact of select factors on the prices of gold in Malaysia. The study used Multiple Linear Regression Model to determined significant relationship between dependent and independent variables, covering data for 8 years period which are from 2006 to 2013. The researcher used four independent variables that affect the prices of gold which are exchange rate, inflation rate, crude oil price, and silver price.The empirical results have found there is positively significant relationship between crude oil prices and silver prices towards gold prices, while inflation rate is negatively significant. However, this study found that there is no significant between exchange rate and gold prices. The results of the study are valuable for both academic and investor.